Hubungan Tingkat Pengetahuan dan Persepsi Terhadap Perilaku Safety Riding pada Pengendara Ojek Online di Kota Palembang - Berlicia, Ida; Camelia, Anita (Poltekkes Kemenkes Kendari, 2023)
Knowledge and perception about safety riding in a company is very important to prevent work accidents, because knowledge and perception can influence safety riding behavior while working. The number of accidents in Palembang City involving motorbikes in January-September was 1,708 cases. Traffic accidents are also a risk for online motorcycle taxi drivers in Palembang City. This research aims to determine the relationship between knowledge, perception, gender, education, driving experience, age, personal protective equipment, salary system and online motorcycle taxi driving safety behavior in Palembang City. This type of research is an analytical survey with a cross-sectional design. This research was conducted on online motorcycle taxi workers in Palembang City with a sample of 104 people. The sampling method is Accidental Sampling. Data analysis used the chi square test. The research results showed that as many as 94.2% of online motorcycle taxi drivers had high knowledge and as many as 97.1% of online motorcycle taxi drivers in Palembang City had a positive perception of safety riding behavior. It is known that ? = 0.05 shows that there is a relationship between knowledge, perception, level of education, protective riding equipment and safety riding behavior.